Effect of heat source direction on the thermal performance of phase change material (PCM) based thermal control module (TCM) under the influence of low gravity environment. (November 2021) - Kansara, Keyur; Singh, V.K.
Abstract: For improving thermal management of electronic components/detectors, a novel phase change material based thermal control module is investigated to analyze the effect of heat source direction on the melting and solidification of PCM in a three-dimensional domain under the influence of low gravity environment. A distinctive method of inverting the PCM-based TCM against gravity is proposed to analyze the direction of heat source in two cases (non-inverted and inverted). The melting of PCM is simulated at different gravitational acceleration values (i.e., g, g/2, g/10, g/20, g/40, g/80) for both the inverted and non-inverted cases. The enthalpy-porosity method is employed to investigate the melting and solidification processes. The results show that inverting the heat source direction significantly affects the thermal performance of the PCM-based TCM. The maximum and minimum difference in the average liquid fraction value between the two cases is observed to be 13.63% and <2% at (g) and (g/80). The difference in the source temperature between the inverted and non-inverted cases varies between 3.3% to 19.68% when the gravitational acceleration increases from g/80 to g. The minuscule discrepancy (< 3%) in average liquid fraction indicates that the solidification of PCM is minimally affected by inverting heat flow direction.